2016
DOI: 10.1038/ncomms13249
|View full text |Cite
|
Sign up to set email alerts
|

Basal forebrain degeneration precedes and predicts the cortical spread of Alzheimer’s pathology

Abstract: There is considerable debate whether Alzheimer's disease (AD) originates in basal forebrain or entorhinal cortex. Here we examined whether longitudinal decreases in basal forebrain and entorhinal cortex grey matter volume were interdependent and sequential. In a large cohort of age-matched older adults ranging from cognitively normal to AD, we demonstrate that basal forebrain volume predicts longitudinal entorhinal degeneration. Models of parallel degeneration or entorhinal origin received negligible support. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
196
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(216 citation statements)
references
References 68 publications
18
196
2
Order By: Relevance
“…Our study paves the way for using rs‐fMRI‐based assessments of subregion‐specific CBF function to complement established volumetric approaches in the in vivo study of CBF involvement in cognitive aging and neurodegenerative disease (Grothe, Heinsen, & Teipel, ; Schmitz & Spreng, ). As a first step toward such applications, we demonstrated that the dissociated FC profiles of the identified CBF subdivisions are reproducible in rs‐fMRI acquisitions of elderly participants as typically collected in clinical research settings.…”
Section: Resultsmentioning
confidence: 91%
“…Our study paves the way for using rs‐fMRI‐based assessments of subregion‐specific CBF function to complement established volumetric approaches in the in vivo study of CBF involvement in cognitive aging and neurodegenerative disease (Grothe, Heinsen, & Teipel, ; Schmitz & Spreng, ). As a first step toward such applications, we demonstrated that the dissociated FC profiles of the identified CBF subdivisions are reproducible in rs‐fMRI acquisitions of elderly participants as typically collected in clinical research settings.…”
Section: Resultsmentioning
confidence: 91%
“…Delayed memory functions such as those reflected by the MMSE word recall have been associated with three neuroanatomic regions within the brain (and the pathways that interconnect them). These are the medial temporal lobe (hippocampus, entorhinal cortex [37, 38, 39], the thalamus (dorsomedial, anterior nuclei [40, 41]) and the basal forebrain which innervates the hippocampus with essential cholinergic neurons [42,43,44]. Executive functions, particularly those involving processing speed and mental flexibility (i.e., working memory such as counting backwards or spelling a word backwards), are most commonly associated with the frontal cortex [45, 46] and subcortical nuclei (e.g., caudate, thalamus, and associated frontal-subcortical and frontal-parietal white matter connections [47]).…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of BFCS nuclei has been developed and validated as a highly relevant and robust region of interest for automatic structural MRI assessment of atrophy rate of change from the preclinical to the clinical AD stages [160, 162167]. Evidence indicates that the BFCS may even degenerate before medio-temporal lobe structures, as early as at the preclinical stage [163, 168]. In contrast to the hippocampal volume, the atrophy of BFCS was significantly correlated to in vivo brain amyloid load in AD and non-demented elderly individuals [169, 170].…”
Section: Contribution and Role Of Structural Magnetic Resonance Imagimentioning
confidence: 99%